2005
DOI: 10.1086/430943
|View full text |Cite
|
Sign up to set email alerts
|

AnXMM‐NewtonView of the Soft Gamma Repeater SGR 1806−20: Long‐Term Variability in the Pre–Giant Flare Epoch

Abstract: The low-energy (<10 keV) X-ray emission of the soft gamma repeater SGR 1806À20 has been studied by means of four XMM-Newton observations carried out in the last two years, the latest performed in response to a strong sequence of hard X-ray bursts observed on 2004 October 5. The source was caught in different states of activity; over the [2003][2004] period, the 2-10 keV flux doubled with respect to the historical level observed previously. The long-term rise in luminosity was accompanied by a gradual hardening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
102
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 34 publications
17
102
1
Order By: Relevance
“…It connects rather well with the low energy (< 10 keV) spectrum [32], and the intensity and spectral hardness are correlated with the degree of bursting activity of the source [31,8] and with the flux of the recently discovered IR counterpart of the source [17]. Our group is continuosly monitoring the hard X-ray flux of SGR 1806-20, and the long term light curve of the source is shown in This behaviour can be interpreted, as an increase of the twist angle in the magnetar magnetic field, which in turn increases the burst emission rate and the multiple resonant cyclotron scattering, which produces harder spectra, as predicted by [46].…”
Section: Discovery Of the Persistent Emissionsupporting
confidence: 65%
“…It connects rather well with the low energy (< 10 keV) spectrum [32], and the intensity and spectral hardness are correlated with the degree of bursting activity of the source [31,8] and with the flux of the recently discovered IR counterpart of the source [17]. Our group is continuosly monitoring the hard X-ray flux of SGR 1806-20, and the long term light curve of the source is shown in This behaviour can be interpreted, as an increase of the twist angle in the magnetar magnetic field, which in turn increases the burst emission rate and the multiple resonant cyclotron scattering, which produces harder spectra, as predicted by [46].…”
Section: Discovery Of the Persistent Emissionsupporting
confidence: 65%
“…3) at least when the spectral deformation resulting from the resonant scattering process is computed in the simple way proposed by Lyutikov and Gavriil (2006). However, it is worth noting that, at variance with 1E 1048-56, these two sources exhibit strong high-energy power-law tails which extend up to the γ -rays (Kuiper et al 2006;Molkov et al 2005;Mereghetti et al 2005a). Motivated by that, we fitted the whole 1-50 keV spectra with the RCS model plus a power-law.…”
Section: Preliminary Resultsmentioning
confidence: 97%
“…Magnetars candidates are strong X-ray sources, and their X-ray spectra in the 0.5-10 keV band are usually fit with a two component model consisting of (besides interstellar absorption) a thermal blackbody with a typical temperature kT ∼ 0.3-0.4 keV and a power-law with a relatively steep photon index, Γ ∼ 2-4 (see Kaspi 2006 in this volume, andWoods andThompson 2004 for recent reviews). In some cases, SGR spectra have been fit with a single power-law component, but recent longer observations showed that, also for these sources, a blackbody component is often required (Mereghetti et al 2005a(Mereghetti et al , 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…for a single interesting parameter (b) Radius at infinity assuming a distance of 15 kpc (c) Absorbed flux in the 2-10 keV energy range (Mereghetti et al 2005c). At the time of the giant flare the source was not visible by XMM-Newton (and most other satellites) due to its proximity to the Sun, thus the next observation could be done only in March 2005 (Tiengo et al 2005).…”
Section: Xmm-newton Resultsmentioning
confidence: 99%
“…Although the deviation is formally at 3.3σ, it could not be reproduced in spectra obtained with different data selections and binning criteria. Therefore we consider it as only a marginal evidence for an absorption line (Mereghetti et al 2005c). …”
Section: Xmm-newton Results On the Sgrs Burstsmentioning
confidence: 99%